* A = √(6 - 2√5) + √(9 - 4√5)
= √(1² - 2.1.√5 + (√5)²) + √(2² - 2.2.√5 + (√5)²)
= √(1 - √5)² + √(2 - √5)²
= |1 - √5| + |2 - √5|
= √5 - 1 + √5 - 2
= 2√5 - 3
* A = √(7 - 4√3 )- √(4 - 2√3)
= √(2² - 2.2.√3 + (√3)²) - √(1² - 2.1.√3 + (√3)²)
= √(2 - √3)² - √(1 - √3)²
= |2 - √3| - |1 - √3|
= 2 - √3 - (√3 - 1)
= 3 - 2√3
* A = √(7 - 2√6) - √(7 + 2√6)
= √(1² - 2.1.√6 + (√6)²) - √(1² + 2.1.√6 + (√6)²)
= √(1 - √6)² - √(1 + √6)²
= |1 - √6| - |1 + √6|
= √6 - 1 - (√6 + 1)
= -2
* A = √(11 + 6√2 )- √(11 - 6√2)
= √(3² + 2.3.√2 + (√2)²) - √(3² - 2.3.√2 + (√2)²)
= √(3 + √2)² - √(3 - √2)²
= |3 + √2| - |3 - √2|
= 3 + √2 - (3 - √2)
= 2√2
* a = √(18 + 8√2 )+ √(18 - 8√2)
= √(4² + 2.4.√2 + (√2)²) + √(4² - 2.4.√2 + (√2)²)
= √(4 + √2)² + √(4 - √2)²
= |4 + √2| + |4 - √2|
= 4 + √2 + 4 - √2
= 8
* a = căn(4 - 2√3) + √(4 + 2√3)
= √(1² - 2.1.√3 + (√3)²) + √(1² + 2.1.√3 + (√3)²)
= √(1 - √3)² + √(1 + √3)²
= |1 - √3| + |1 + √3|
= √3 - 1 + √3 + 1
= 2√3
* a = √(4 + 2√3) - √(4 - 2√3)
= √(1² + 2.1.√3 + (√3)²) - √(1² - 2.1.√3 + (√3)²)
= √(1 + √3)² - √(1 - √3)² = |1 + √3| - |1 - √3|
= 1 + √3 - (√3 - 1)
= 2
* a = √(3+2√2)+√(3-2√2)
= √(1² + 2.1.√2 + (√2)²) + √(1² - 2.1.√2 + (√2)²)
= √(1 + √2)² + √(1 - √2)²
= |1 + √2| + |1 - √2|
= 1 + √2 + √2 - 1
= 2√2
* a = √(8 - 2√7) - √(8 + 2√7)
= √(1² - 2.1.√7 + (√7)²) - √(1² + 2.1.√7 + (√7)²)
= √(1 - √7)² - √(1 + √7)²
= |1 - √7| - |1 + √7|
= √7 - 1 - (√7 + 1)
= -2
* a = √(28 + 10√3) + √(19 - 8√3)
= √(5² + 2.5.√3 + (√3)²) + √(4² - 2.4.√3 + (√3)²)
= √(5 + √3)² + √(4 - √3)²
= |5 + √3| + |4 - √3|
= 5 + √3 + 4 - √3
= 9